2011
DOI: 10.4297/najms.2011.385
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of suture material and technique of closure of subcutaneous fat and skin in caesarean section

Abstract: Background:A large number of women undergo caesarean section throughout the world. These women pass through a period of post operative pain and a morbidity period. These women translate into a substantial portion of population and hence there is a load on the financial resources of healthcare system. Use of the appropriate technique to approximate the wound after caesarean section would not only avoid financial load but also help in early recovery of the patient.Aim:The aim of this study is to compare the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…The goals of wound closure include obliteration of dead space, even distribution of tension along deep suture lines, and maintenance of tensile strength across the wound. 5 Many techniques and suture materials have been tried to achieve closure and restore the structural and functional anatomy of skin. Suture materials that have been tried are natural and synthetic materials, which are absorbable and non-absorbable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of wound closure include obliteration of dead space, even distribution of tension along deep suture lines, and maintenance of tensile strength across the wound. 5 Many techniques and suture materials have been tried to achieve closure and restore the structural and functional anatomy of skin. Suture materials that have been tried are natural and synthetic materials, which are absorbable and non-absorbable.…”
Section: Introductionmentioning
confidence: 99%
“…9 Best ways to close skin incisions for optimal results are still under experimentation. 5,10 There is a need to identify the right method and suture material to provide the best wound outcomes. The method should have less postoperative morbidity, help faster recovery and be cost effective at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…6,[9][10][11][12][13] This variation probably results from several factors in the various studies. [9][10][11][12][13] Firstly, studies with broad exclusion criteria have lower wound complication rates than studies with stringent exclusion criteria. The wound complication rate in our study was 7%, with the only exclusion criterion being declining to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, studies (including our study) in which the subcutaneous fat layer was sutured prior to skin closure, reported lower wound complication rates than those in which the subcutaneous fat layer had not been sutured. 4,6,11 A limitation of our study was that we did not measure BMI and therefore did not compare wound infection rates in different BMI groupings. The mean weights in all 3 groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…These women pass through a period of postoperative pain and a morbidity period. Use of the appropriate technique to approximate the wound after caesarean section would not only avoid financial load but also help in early recovery of the patient 5 . The best way of closing the mother's skin layer after caesarean section has been a topic of debate.…”
Section: Research Articlementioning
confidence: 99%